Feasibility of spectral analysis techniques for disruption analysis in Aditya tokamak - Thaj Mary Delsy, T; M. Nandhitha, N; Sheela Rani, B (International Journal of Engineering and Technology, 2018)
Aditya Tokamak is a medium size fusion reactor that uses plasma for the generation of power. Magnetic fields are used to confine plasma inside the torus. Release of plasma from its confinement is called plasma disruption. Plasma disruption is a dangerous event, which damages the in â€“ vessel components of the Tokamak. So the early stage prediction of plasma disruption is quite important. Wavelet transform is a powerful tool for the analysis of the non - stationary signals. In this paper, analysis of plasma disruption signals using Biorthogonal wavelet transforms is perform to identify disruption. Plasma current, Vloop, Halpha, Hard X ray, Mirnov coil signal, Soft X-ray are diagnostic signals. Performance is measured in terms of sensitivity and specificity.Â Â
Keywords: Biorthogonal Wavelet; Tokamak; Diagnostic Signals; Skewness; Sensitivity.